Att närma sig Boden - Arvidsson, Viktoria; Karlsson, Stina (SLU/Dept. of Landscape Architecture, Planning and Management (from 130101), 2006)
Approaching Boden deals with the approaching of a city, both in a physical sense – along the road – and in a spiritual sense – in mind. The physical encounter with a city is represented by the experience of the road and its surroundings, while the spiritual encounter is represented by the idea of the city that we already have, or will get, in our minds. We have in this degree project approached Boden through a thoroughly analysis of both the entrance roads and the city itself. In this degree project we are looking for ways of how to create characteristic and interesting entrance roads to a city, with Boden as an example. This demands knowledge about the problems involving entrance roads as well as the distinctive features of the city. Studies of earlier projects dealing with entrance roads show examples of how these problems can be solved. The two analyses methods City Analysis and Character Analysis of Entrance Roads work as important complement to each other. The City Analysis gives an understanding of the identity of the city, through its history, form and the development of its physical shape. On the other hand the Character Analysis of Entrance Roads shows the most valuable characters and biggest problems close to the road. To show the importance of gathering and integrating different projects and visions, a number of a current road- and city building projects that also concern Boden and its entrance roads will be presented. With this material as a starting point a Design Program for the Entrances of Boden has been developed, as well as an alternative road building for the most used entrance road, road 97 from Luleå. These proposals are all trying to simplify and strengthen the experience of approaching Boden. Att närma sig Boden handlar om att närma sig en stad, både i fysisk mening - längs en väg, och mentalt - i tanken. Det fysiska mötet med staden består i den direkta upplevelsen av miljöerna längs och vid sidan av vägen medan det mentala mötet utgörs av själva uppfattningen eller den inre bild vi har ...